Zostera noltii extract lowers blood glucose and restores vascular function in diabetic rats (Bangladesh Journal of Pharmacology, 2014)
The antidiabetic effect of seagrass Zostera noltii extract was investigated through a crosstalk between its antioxidant and vasoprotective properties. The extract was orally administered to alloxan-diabetic rats (50, 150, 250 mg/kg body weight). Serum glucose was determined; liver and kidney functions, body weight, total leukocyte counts were measured; liver oxidative markers were assayed. Acetylcholine, phenylephrine and 5-HT responses were tested. eNOS levels and generation of ROS in aortic tissue were quantified. The extract of Z. noltii lowered blood glucose in all tested dose levels. Extract at a concentration of 50 mg/kg failed to preserve the levels of antioxidants and did not alter lipid peroxidation whereas higher doses improved liver oxidative status. Impaired acetylcholine relaxations, augmented phenylephrine and 5-HT contractions in alloxan-diabetic aortic rings were restored by Z. noltii treatment. This recovery was accompanied by increased eNOS synthesis and a reduction in ROS generation. The extract lowers blood glucose and prevents hyperglycemia-induced endothelial dysfunction in alloxan-diabetic rats.